Association Between Ketosis and Changes in Appetite Markers with Weight Loss Following a Very Low‐Energy Diet. Issue 12 (24th November 2020) - Martins, Catia; Nymo, Siren; Truby, Helen; Rehfeld, Jens F.; Hunter, Gary R.; Gower, Barbara A.
Abstract : Objective: The purpose of this study was to examine whether the degree of ketosis, measured as plasma β‐hydroxybutyrate (βHB) in fasting, was associated with changes in appetite feelings and plasma concentration of appetite‐related hormones after weight loss. Methods: A total of 87 individuals with obesity (BMI: 36.5 ± 4.0 kg/m 2 ; age: 42.4 ± 9.7 years; 39 males) underwent 8 weeks of a very low‐energy diet. Body weight/composition, plasma concentration of βHB, and appetite‐related hormones (active ghrelin, active glucagon‐like peptide 1 [GLP‐1], total peptide YY, cholecystokinin [CCK], and insulin) and subjective appetite feelings were measured at baseline and week 9. Results: Participants lost 17.7 ± 4.1 kg and were ketotic (βHB: 1.24 ± 0.82 mmol/L in fasting) at week 9. A negative association was found between βHB in fasting at week 9 and changes in basal ( r  = −0.315, P  = 0.003) and postprandial ghrelin concentration ( r  = −0.286, P  = 0.008), and a positive association was found with the change in postprandial GLP‐1 ( r  = 0.244, P  = 0.025) and CCK ( r  = 0.228, P  = 0.035). No association was seen between βHB in fasting and changes in peptide YY or subjective feelings of appetite. Conclusions: βHB plasma concentration in fasting is associated with lower concentrations of the hunger hormone ghrelin and increased concentrations of the satiety hormones GLP‐1 and CCK. Future studies should explore the molecular mechanisms by which βHB modulates the secretion of gut hormones.